2020
DOI: 10.5817/cp2020-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Instagram selfie-posting and young women’s body dissatisfaction: Investigating the role of self-esteem and need for popularity

Abstract: An online survey was conducted to explore how Instagram users’ selfie-posting behavior affects their self-esteem and body dissatisfaction. Female college students from South Korea (N = 321) participated in the survey. Results showed that Instagram users’ selfie-posting was positively related to their self-esteem. Moreover, Instagram users’ self-esteem mediated the relationship between their selfie-posting behavior and body dissatisfaction. Findings showed that Instagram users’ selfie-posting behavior may posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 58 publications
4
15
0
2
Order By: Relevance
“…These results partially contrast with our hypotheses and previous studies (Lyu et al, 2022); but they are consistent with previous research that did not document a direct effect of selfie-posting on body image concerns (Kim, 2020). Furthermore, several studies identified few factors (e.g., self-esteem, social comparison, or appearance-based feedback; Bailey & Ricciardelli, 2010; Kim, 2020), which may result in different consequences among people who spend much time showing up as their best on SNS. In particular, consistent with Festinger’s (1954) theory, people who often share their selfies engage more frequently in social comparison in the context of SNS (Chae, 2017; Lee & Lee, 2021) to evaluate themselves based on a significant domain to them: physical attractiveness.…”
Section: Discussionsupporting
confidence: 77%
“…These results partially contrast with our hypotheses and previous studies (Lyu et al, 2022); but they are consistent with previous research that did not document a direct effect of selfie-posting on body image concerns (Kim, 2020). Furthermore, several studies identified few factors (e.g., self-esteem, social comparison, or appearance-based feedback; Bailey & Ricciardelli, 2010; Kim, 2020), which may result in different consequences among people who spend much time showing up as their best on SNS. In particular, consistent with Festinger’s (1954) theory, people who often share their selfies engage more frequently in social comparison in the context of SNS (Chae, 2017; Lee & Lee, 2021) to evaluate themselves based on a significant domain to them: physical attractiveness.…”
Section: Discussionsupporting
confidence: 77%
“…This study first investigated the underlined mechanism of why social media users post a selfie-and what are the significant predictors of selfie-posting behavior? Past research emphasizes selfie-posting behavior on body satisfaction Lee & Lee, 2021;Lonergan et al, 2019) and the need for popularity (Utz et al, 2012;Kim, 2020). This study demonstrated that self-esteem and narcissism are the significant predictors of exhibitionism and selfie-posting behavior.…”
Section: Theoretical and Managerial Implications Theoretical Implicat...supporting
confidence: 48%
“…It has been shown that the visualization and exposure to attractive peers through SM contributes to the development of a negative body image (Hogue & Mills, 2019;Kim, 2020), together with the photographic selfretouching performed by SM users (Mills et al, 2018). SM images are powerful tools not only for communicating but also for perpetuating ideals that influence adolescents' sense of identity.…”
Section: Involvement Of Social Media In Body Dissatisfaction and Eating Disorder Psychopathologymentioning
confidence: 99%